Предмет: Алгебра,
автор: Strelok57
1.Упростить Выражение:
(У-8)(У+8)-3у(у+2)
2.Решите уравнение:
(Х-1)(Х+1)-х^2=5х-6
Ответы
Автор ответа:
0
(y-8)(y+8)-3y(y+2)=y^2-64-3y^2-6y=-2y^2-6y-64
Автор ответа:
0
(x-1)(x+1)-x^2=5x-6
Автор ответа:
0
x^2-1-x^2=5x-6
Автор ответа:
0
5x=-5
Автор ответа:
0
x=-1
Похожие вопросы
Предмет: Английский язык,
автор: aaaa484884
Предмет: Биология,
автор: nazarovtimur07
Предмет: История,
автор: mariayacenko24
Предмет: Математика,
автор: Аноним
Предмет: Информатика,
автор: vitekdobrioglo